Frequency-coded spatiotemporal control of telencephalic ictal oscillations and inter-cortical coherence by thalamus - Ping Chou; Yi-Chen Lai; Yen-Hsin Zheng; Ya-Chin Yang; Chung-Chin Kuo (Neurobiology of Disease)
Many epileptic seizures (hereafter abbreviated as seizures) are characterized by overly synchronized oscillating activities in the thalamocortical system. Despite dense reciprocal innervation between cortex and thalamus, the exact role of thalamus in ictogenesis (e.g. as a passive associate, lenient modulator, or indispensable controller) has been unsettled. We found that either electrical or chemical ictogenic stimulation of basolateral amygdala (BLA) induces augmentation of δ-frequency local field potential (LFP) oscillations in situ. In contrast, the thalamic mediodorsal nucleus (MD), which is reciprocally connected with BLA, responds with mixed θ-α and δ oscillations at first. MD may then be entrained more and more into the latter, leading to augmented δ oscillations as well as δ coherence in the thalamocortical system and maximal behavioral seizures. Inhibition of MD with topical tetrodotoxin dissipates the coherent δ augmentation and decreases multi-unit spikes in BLA and other telencephalic areas, suggesting critical involvement of MD in the inter-cortical communication and focal ictogenesis. Systemic application of proconvulsant pentylenentetrazol could induce interchanging periods of δ and θ-α augmentation in MD, at which periods concomitant electrical stimulation of BLA would be much more and less likely to induce seizures, respectively. The mechanism underlying thalamic δ entrainment in telencephalic ictogenesis and “θ-α antagonism” may involve local GABA-glutamate interactions and the requirement of cortical glutamatergic input for the generation of thalamic burst discharges (“relay bursts''). Thalamus thus assumes a critical control of the temporal pace and spatial scale of telencephalic oscillations, with a specific but well adaptable order of frequency and amplitude modulation.